2020
DOI: 10.1002/dvdy.245
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the regenerative capacity and growth patterns of the Texas blind salamander (Eurycea rathbuni)

Abstract: Background: Regeneration of complex patterned structures is well described among, although limited to a small sampling of, amphibians. This limitation impedes our understanding of the full range of regenerative competencies within this class of vertebrates, according to phylogeny, developmental life stage, and age. To broaden the phylogenetic breath of this research, we characterized the regenerative capacity of the Texas blind salamander (Eurycea rathbuni), a protected salamander native to the Edwards Aquifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…This hypothesis needs further exploration since we found that amphibians had lower neoplasia and cancer prevalence than mammals and squamates, but higher than birds. Regenerative capacities are not uniform across species, orders, and life-stages of amphibians 32 , possibly explaining why neoplasia and cancer prevalence is relatively high in this group. Finally, we found that neoplasia, cancer, and malignancy transformation rates are remarkably frequent in snakes and occurred in almost all snake families included in this study, which is similar to 18 .…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis needs further exploration since we found that amphibians had lower neoplasia and cancer prevalence than mammals and squamates, but higher than birds. Regenerative capacities are not uniform across species, orders, and life-stages of amphibians 32 , possibly explaining why neoplasia and cancer prevalence is relatively high in this group. Finally, we found that neoplasia, cancer, and malignancy transformation rates are remarkably frequent in snakes and occurred in almost all snake families included in this study, which is similar to 18 .…”
Section: Discussionmentioning
confidence: 99%
“…As in other cave dwelling organisms, sexual maturity is delayed and reproductive output is reduced (Culver & Pipan, 2019). Females begin to show small eggs at 1.5-2 years of age at the SMARC (Vieira et al, 2020). However, the presence of eggs does not necessarily result in the production of offspring.…”
Section: Introduction and Purposementioning
confidence: 96%
“…Survival in the wild is greater than 10 years (Longley, 1978), though we estimate survival may extend upwards of 30 years based on other cave salamander life histories and the age of captive individuals. Growth rate drastically decreases with age and size, but is overall indeterminate (Vieira et al, 2020).…”
Section: Introduction and Purposementioning
confidence: 96%
“…Subtle differences in limb regeneration have also been reported among the various species of urodeles, highlighting the importance of more diverse sampling from this order. With this in mind, Vieira et al teamed up with the US Fish and Wildlife Service in San Marcos Texas to characterize limb and tail regeneration in the Texas blind salamander ( Eurycea rathbuni ), a threatened cave‐dwelling and aquatic species 3 . In addition to charactering blastema formation and regeneration in this species for the first time, the team documented multiple aspects of this species biology including methods of sexing, mating behavior, and details of animal husbandry to encourage the research community to adopt this species as a regenerative model organism.…”
mentioning
confidence: 99%